THE SOCIOLINGUISTIC ASPECT OF THE CONSIDERATION OF THE LEXICAL LEVEL OF THE PLAN OF EXPRESSION OF THE GENRE OF LITERARY TEXTS BY J. D. PASSOS AS A WRITER OF THE GROUP "LOST GENERATION" - Irina O. Mazirka; Lyudmila A. Stativka (Вестник Московского государственного областного университета, 2023)
<!DOCTYPE html> Aim. To prove from the standpoint of sociolinguistics, namely, from the plan of genre expression of the works of J. D. Passos at the lexical level, the affiliation of the writer's literary texts of the 20s - 30s of the twentieth century to the texts of the group of American authors of the “lost generation” of the same period of time. Methodology. Applying the method of contextual analysis of a literary text and based on the vocabulary selected by us earlier by the method of continuous sampling, we analyze the text using descriptive and comparative methods. The counting of the selected tokens is carried out through the use of a quantitative method, after which the results of the study are interpreted. Results. Having considered, within the framework of sociolinguistics, the lexical level of the genre expression plan in the four works of J.D. Passos and having analyzed the lexemes “war” and “idleness” that are in the field of the main social contexts, we proved that the plan of expression at this level in the works of J. D. Passos, in general, coincides with the plan of expression of the texts of the group of “the lost generation”, so in this aspect we can suppose the affiliation of not only the literary texts of J.D. Passos (lexical level), but also the writer himself with the mentioned group of writers from the standpoint of social linguistics as well. Research implications. The results obtained show the importance of applying the methods of sociolinguistic analysis of the literary texts genre to isolate socially marked vocabulary in them, which makes it possible to identify and meaningfully interpret new social knowledge in other texts and by other authors. The application of this method lies in explaining social reality, actions of participants in communicative contexts in the general social context will help better understand the history and culture of the country and its priorities.